Kesalahan Penggunaan Kalimat dalam Buku Ensiklopedia Kerajaan Islam di Indonesia - Via Aulia; Novidya Choirina Priyandini; Sinta Nur Hikmah; Azzahra Isnaini; Adellia Intan Maharani; Asep Purwo Yudi Utomo; Amilia Buana Dewi Islamy; Riyadi Widhiyanto (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2026)
Language is a means of communication between individuals and groups to convey ideas, concepts, or insights. Language can be expressed orally or in writing. Spoken language is temporary or contemporary, while written language is permanent. Spoken language is delivered without an intermediary media, whereas writing serves as an academic archive to ensure that the conveyed insights are preserved. Therefore, writing is done, for example, in encyclopedias, which contain collections of information about science, knowledge, history, arts, technology, and others in a broad and easily understandable manner. Writing books is very important in delivering accurate and easily understood information, so the use of language must adhere to linguistic rules. However, errors are often found that can disrupt clarity and accuracy of information. This research aims to identify types of sentence errors in the encyclopedia book titled “Islamic Kingdoms in Indonesia.” The study examines the use of language in accordance with linguistic rules using a qualitative method and a descriptive approach, analyzing data from various chapters in the book in depth. The results show errors in sentence structure, punctuation, and incorrect terminology, which can reduce the quality of the information. The benefit of this research is to provide recommendations for writers and publishers to improve the encyclopedia so that it becomes more informative and easier to understand, as well as to enhance the quality of scholarly works in the field of historiography.